1991
DOI: 10.1044/jshr.3406.1387
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Averaged Potentials Preceding Oral Movement

Abstract: The “readiness potential” is an event-related potential that shows increasing negativity at vertex and motor strip scalp recording sites prior to voluntary, unilateral limb movements. Though speech involves movement on both sides of the midline, recent recordings of prespeech potentials suggest a pattern of bilateral activation that lateralizes to the dominant hemisphere just prior to the onset of articulatory movement. To determine whether this pattern of dominant hemisphere activation is present prior to a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…While many unresolved issues remain with respect to the control of tongue movements, the bilateral control has been consistently reported in earlier studies (e.g., Wohlert and Larson, 1991), in agreement with the prominent power change over the central regions of the motor cortex in the present study.…”
Section: Resultssupporting
confidence: 93%
“…While many unresolved issues remain with respect to the control of tongue movements, the bilateral control has been consistently reported in earlier studies (e.g., Wohlert and Larson, 1991), in agreement with the prominent power change over the central regions of the motor cortex in the present study.…”
Section: Resultssupporting
confidence: 93%
“…Since Kornhuber and Deecke (1965) recorded the Bereitschaftspotential (BP) or readiness potential (RP), related to simple and self-paced movements, several studies have been carried out in which four MRCPs have consistently been recorded: the first component of the readiness potential (1st-RP), the negative slope (NS'), the motor potential (MP) and the reafferent potential (RAP) (for a complete revision, see Shibasaki and Hallett, 2006). On the other hand, the speech MRCPs have been less well studied, and there is only conclusive data regarding the 1st-RP component (Brooker and Donald, 1980;Deecke et al, 1986;Grabow and Elliott, 1974;Grözinger et al, 1975Grözinger et al, , 1977Levy, 1977;McAdam and Whitaker, 1971;Tarkka, 2001;Wohlert, 1993;Wohlert and Larson, 1991).…”
Section: Introductionmentioning
confidence: 97%
“…Lip protrusion is a midline movement, and therefore probably involves an equivalent contribution from the cerebral sensorimotor cortex of both sides. An electroencephalographic (EEG) study reported that non-speech movement of a midline structure was under bilateral cortical control, and that control of lip movement was apparently not necessarily a dominant hemisphere function (Wohlert and Larson 1991). Salmelin et al also reported in an MEG study that no interhemispheric correlations were found for the non-verbal mouth movements (Salmelin and Sams 2002).…”
Section: Discussionmentioning
confidence: 97%